Group B streptococci colonization in pregnant women: risk factors and evaluation of the vaginal flora - Rocchetti, Talita T. [UNESP]; Marconi, Camila [UNESP]; Rall, Vera L. M. [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Corrente, José Eduardo [UNESP]; da Silva, Marcia [UNESP] (Springer Heidelberg, 2011)
To determine the prevalence of group B streptococci (GBS) in our population, and to assess the association between risk factors and vaginal flora with maternal rectovaginal colonization.Samples were obtained from 405 patients between 35 and 37 weeks of gestation. Swabs from the vaginal and perianal regions were cultured in Todd Hewitt and subcultured in blood agar. Colonies suggestive of GBS were submitted to catalase and CAMP test. The vaginal flora was evaluated on Gram stain vaginal smears. Socio-demographic and obstetric data were obtained by designed form. Considering maternal GBS colonization as the response variable, a logistic regression model was fitted by the stepwise method with quantitative and qualitative explanatory variables.The prevalence of GBS colonization was 25.4%. The most frequent vaginal flora abnormalities were cytolytic vaginosis (11.3%), followed by bacterial vaginosis (10.9%), candidosis (8.2%) and intermediate vaginal flora II (8.1%). Logistic regression analysis revealed that maternal age, number of sexual intercourse/week, occurrence of previous spontaneous abortion, presence of candidosis and cytolytic vaginosis were associated with streptococcal colonization.The prevalence of GBS is high in pregnant women and is associated with sexual intercourse frequency, previous spontaneous abortion and the presence of candidosis or cytolytic vaginosis.
Keywords: Group B streptococci; Pregnancy; Vaginal flora; Risk factors